2004
DOI: 10.1073/pnas.0407611102
|View full text |Cite
|
Sign up to set email alerts
|

Genomic dissection of the cell-type-specification circuit in Saccharomyces cerevisiae

Abstract: The budding yeast Saccharomyces cerevisiae has three cell types (a cells, ␣ cells, and a͞␣ cells), each of which is specified by a unique combination of transcriptional regulators. This transcriptional circuit has served as an important model for understanding basic features of the combinatorial control of transcription and the specification of cell type. Here, using genome-wide chromatin immunoprecipitation, transcriptional profiling, and phylogenetic comparisons, we describe the complete cell-type-specificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 29 publications
3
102
0
4
Order By: Relevance
“…YLR040C has also been shown to be translated by ribosome profiling (Brar et al 2012) and localized to the cell wall (Hamada et al 1999;Giaever et al 2002). Deletion of YLR040C was reported as having no effect on mating (Galgoczy et al 2004). We found that in unstimulated cells the gene is expressed 11-fold more strongly in MATa-playing-a than in MATa cells and that its transcription is not significantly induced when MATa-playing-a cells are exposed to pheromone (see Table S2).…”
Section: Afb1 Encodes a Novel A-factor Barrier Proteinsupporting
confidence: 51%
See 2 more Smart Citations
“…YLR040C has also been shown to be translated by ribosome profiling (Brar et al 2012) and localized to the cell wall (Hamada et al 1999;Giaever et al 2002). Deletion of YLR040C was reported as having no effect on mating (Galgoczy et al 2004). We found that in unstimulated cells the gene is expressed 11-fold more strongly in MATa-playing-a than in MATa cells and that its transcription is not significantly induced when MATa-playing-a cells are exposed to pheromone (see Table S2).…”
Section: Afb1 Encodes a Novel A-factor Barrier Proteinsupporting
confidence: 51%
“…Ten genes fit this criterion and of these, only one, YLR040C, is annotated as encoding a secreted protein that is not already known to be important in mating (Yeast Genome Database at http://www.yeastgenome.org) (see Table S2). (Galgoczy et al 2004), which induces expression of a-specific genes (Strathern et al 1981). YLR040C has also been shown to be translated by ribosome profiling (Brar et al 2012) and localized to the cell wall (Hamada et al 1999;Giaever et al 2002).…”
Section: Afb1 Encodes a Novel A-factor Barrier Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five genes decreased in expression in sir mutants relative to WT strains. We compared this list to known haploid-specific genes as found by chromatin immunoprecipitation of a2 in a/a diploids followed by hybridization of immunoprecipitated DNA to a genome-wide array (Galgoczy et al 2004). That study found 20 haploid-specific genes, all of which were reproduced in our data set (Table 2, genes without footnote markers).…”
Section: At Least 13 Y9 Elements Were Expressedmentioning
confidence: 79%
“…Historically, elucidation of transcriptional regulatory circuits of S. cerevisiae has relied on microarray-based technologies, which are limited in sensitivity and dynamic range (Galgoczy et al 2004). The sensitivity of RNA-Seq and the "pseudodiploid" state of sir mutants allowed us to evaluate the completeness of the identification of cell-type-regulated genes, particularly genes that are potential targets of a1/ a2 and a2/Mcm1 regulation.…”
Section: Discovery Of Novel Haploid-specific Genesmentioning
confidence: 99%